School Direct, a policy for initial teacher training in England: plotting a principled pedagogical path through a changing landscape. Issue 4 (7th August 2016) - Jackson, Alison; Burch, James
Abstract : This paper explores the role of teacher educators in schools and universities in England and the changes that have arisen within the field of initial teacher training (ITT) as a result of the Coalition Government's (2010–2015) School Direct initiative. The discussion which follows and the conclusions suggested are live, current and of pivotal interest to all universities with ITT programmes, as well as all schools involved in the delivery of ITT, and to all parties with a policy interest in the supply of effective teacher education. After setting the context, the discussion starts with a critical examination of ITT policy in England over the course of the last 20 years. We then consider troubling binaries inherent in teacher education and go on to explore insights from research: the importance of beliefs; the problem of enactment; and the theory/practice divide. These insights are then used to craft the enabling constraints for third-space activity designed to set in motion a hybridisation process from which a new breed of teacher educator could emerge. We suggest that university and school colleagues working together in collaborative partnership can provide a principled pedagogical path through a changing landscape of education policy.